2007
DOI: 10.1042/bj20070361
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase-1 is a novel regulator of the interaction between IRBIT and the inositol 1,4,5-trisphosphate receptor

Abstract: IRBIT is an IP3R [IP3 (inositol 1,4,5-trisphosphate) receptor]-binding protein that competes with IP3 for binding to the IP3R. Phosphorylation of IRBIT is essential for the interaction with the IP3R. The unique N-terminal region of IRBIT, residues 1-104 for mouse IRBIT, contains a PEST (Pro-Glu-Ser-Thr) domain with many putative phosphorylation sites. In the present study, we have identified a well-conserved PP1 (protein phosphatase-1)-binding site preceeding this PEST domain which enabled the binding of PP1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 34 publications
1
87
1
Order By: Relevance
“…Phosphorylation at Ser-68 is apparently required for subsequent phosphorylation of Ser-71 and Ser-74. Although the protein kinase phosphorylating Ser-68 in vivo remains unknown, an in silico analysis suggested several candidate protein kinases, including CaMKII (35). Our present study showed that IRBIT-dependent regulation of NHE3 activity was sensitive to the inhibition of CaM and CaMKII.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Phosphorylation at Ser-68 is apparently required for subsequent phosphorylation of Ser-71 and Ser-74. Although the protein kinase phosphorylating Ser-68 in vivo remains unknown, an in silico analysis suggested several candidate protein kinases, including CaMKII (35). Our present study showed that IRBIT-dependent regulation of NHE3 activity was sensitive to the inhibition of CaM and CaMKII.…”
Section: Discussionmentioning
confidence: 51%
“…This NH 2 -terminal region contains a PEST domain enriched with serine residues and phosphorylation of several serine residues is essential for the interaction with IP 3 R (5, 34). A recent study showed that a small region of IRBIT preceding the PEST domain binds protein phosphatase-1, which dephosphorylates Ser-68 of IRBIT, suggesting that IRBIT is regulated by phosphorylation and dephosphorylation (35). Phosphorylation at Ser-68 is apparently required for subsequent phosphorylation of Ser-71 and Ser-74.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the IP3R inhibitory protein, IRBIT, to IP3Rs is also regulated by phosphorylation. 56 Dephosphorylated IRBIT, which might predominate in kinase-inhibited cells, cannot bind to IP3R. As a consequence, the receptor becomes sensitive to IP3 concentrations that exist in cells under resting conditions, which might result in a lower threshold for Ca 2+ release from the NE/ER.…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that the first lysine (K) for the consensus PP1 docking sequence is not included in LongV4. It was reported that the mutation of IRBIT at the PP1 docking site affected the binding affinity of IP 3 R1 (25). The PP1 docking site is located near the multiple phosphorylation sites of the IRBIT family.…”
Section: Discussionmentioning
confidence: 99%